Challenges and Strategies: Curriculum Implementation in 21st Century Learning - Nafisah, Annisa Zauhar; Pahrudin, Agus; Rahmi, Sri (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Education is fundamentally a process of shaping character and developing students' abilities. However, the expected educational outcomes have not been fully achieved, as evidenced by the low academic performance of many students. This study aims to examine aspects of curriculum implementation and the learning process. A qualitative research method was employed using a case study approach. The findings reveal that curriculum implementation, particularly in the learning process, involves student interaction with teachers and engagement with real-world problems both inside and outside the classroom. The stages of curriculum implementation consist of planning, implementation, and evaluation. Several factors hinder effective curriculum implementation, including a lack of teacher innovation, limited teacher skills and knowledge of new methodologies, inadequate facilities, misaligned policies, and low motivation to adopt innovations. Curriculum implementation is influenced by three main factors: curriculum characteristics, implementation strategies, and the characteristics of curriculum users.